Blunted Nocturnal Decline in Blood Pressure - Prisant, L. Michael (J Clin Hypertens (Greenwich), 2007)
Blood pressure normally declines 10%–20% from daytime to sleep. Patients with less than a 10% reduction in daytime blood pressure are referred to as nondippers. A blunted nocturnal decline in blood pressure may be due to diminished sodium excretory capacity, alteration in the autonomic nervous system, or other factors. Secondary hypertension should be considered as a possibility. Target organ damage appears to be more common in nondippers, however, poor reproducibility of nondipping status raises the question as to the appropriate duration of monitoring to establish a diagnosis. Nondippers tend to have a greater reduction in nocturnal blood pressure with nonpharmacologic and pharmacologic treatment.